농산물과 비교한 단기소득 임산물의 FTA 효과 분석 - 이가슬; 임송수; 이상민 (농촌경제, 2015)
The proliferation of free trade agreements (FTAs) appears to ensure mutually favorable trade gains among the bloc economies. Many empirical studies also find net trade creating effects of agricultural trade integration. Nevertheless, there is scant research and understanding regarding preferential trades in non-timber forest products (NTFPs). Establishing a panel data spanning 1995 to 2010 periods for 211 countries, this paper estimated a gravity model with the Heckman estimation, which addresses sample selection bias caused by zero trades. A positively signed and highly significant coefficient for the FTA variable indicates a trade increase of around 13%. This robust and positive trade effect for NTFPs turns out to be greater than the FTA relationship for other agricultural products, which marked only an 8% increase in trade.